INSTRUCTIONAL PLANNING AND PRODUCTIVITY IN PUBLIC SECONDARY SCHOOLS IN ONDO STATE, NIGERIA - Adeolu Joshua Ayeni (Journal of Management and Business Education, 2022)
Stakeholders’ concern about the dwindling quality of teachers’ instructional tasks and students’ academic performance in Nigeria secondary schools could be attributed to the perceive inadequacies in instructional planning. This study therefore investigated teachers’ instructional planning and productivity in public secondary schools in Ondo North Senatorial District of Ondo State, Nigeria. Descriptive survey research design was adopted, and 600 teachers and 30 principals were sampled using multi-stage and simple randomly sampling techniques. Data were collected using Instructional Planning Questionnaire (IPQ), and Teachers’ Productivity Questionnaire (TPQ). Three research questions and two hypotheses guided the study. The research questions were answered using descriptive statistics while the hypotheses were tested at 0.05 level of significance using Pearson Product Moment Correlation (PPMC). Results indicated a moderate level of teachers’ instructional planning (Mean = 2.97); teachers demonstrated high performance in the preparation of lesson notes, content knowledge, classroom management and record-keeping while the least performed tasks included the use of instructional materials, learners’ assessment, performance feedback and review of academic activities. Teachers’ instructional planning has significant relationship with instructional task performance [r = 0.896 p<0.05], and students’ academic performance [r = 0.851 p<0.05]. The study concluded that teachers performed instructional planning at a moderate level while concerted efforts are needed to boost productivity. It was recommended that the State Ministry of Education and relevant professional bodies should organize capacity training seminars/workshops to improve teachers’ instructional tasks performance in secondary schools.